Crystalline structure and remarkably enhanced tensile property of β-isotactic polypropylene via overflow microinjection molding. (July 2019) - Liu, Zhongzhu; Liu, Xianhu; Li, Lele; Zheng, Guoqiang; Liu, Chuntai; Qin, Qi; Mi, Liwei
Abstract: In this work, the β-nucleating agent (β-NA) filled isotactic polypropylene (iPP) parts were prepared via an overflow microinjection molding (OMM). All OMM parts show an obvious skin-core structure. With increasing the β-NA content, the shear layers with highly oriented shish-kebab structure are progressively thickened, resulting in an effective improvement in tensile strength. Specifically, a maximum tensile strength of 69.8 MPa is observed in the OMM sample with 0.2 wt% of β-NA. Moreover, the elongation at break gradually increases with increasing β-NA content, which is ascribed to the increase of β-crystal content. This study gives more insights into the microstructures of β-nucleated iPP microparts processed under intense shear flow, which could open a promising door to optimize the properties of microparts. Graphical abstract: Image 1